Society of Composers, Authors and Music Publishers of Canada v. Entertainment Software Association. - Majekolagbe, Faith O. (American Journal of International Law, 2023)
The article discusses the Supreme Court of Canada's judgment in the case Society of Composers, Authors and Music Publishers of Canada v. Entertainment Software Association regarding states' enactment of rights to protect the interest of authors in the online publication of their copyrighted works.